BIM backed decision support system in the management of heritage building - Mustafa, Muhammad Hadi; Ali, Maisarah; Mohd Ismail, Kamsiah; Hashim, Khairusy Syakirin Has-Yun; Mohamad Suhaimi, Mohamad Saifulnizam (Penerbit UTM Press, 2019)
Historical buildings are always at risk to great danger strike by fire, flood and other potential disasters affecting the building conditions. Thus positive and continuous actions need to be taken to preserve the heritage buildings or else a country might lose its cultural heritage value. In managing historic buildings, managers are often faced with complex decision-making process due to limited or unavailability of reliable information. The absence of such information influenced the way decision making and problem-solving made by the managers. This paper aims to highlight the potentials of Building Information Modelling (BIM) as a decision support system for cultural heritage management. An embedded case study was conducted on Istana Balai Besar Kota Bharu, focusing on the changes of the historical building's layout to demonstrate the ontology. A measured drawing dated back in 1976 was used together with the terrestrial laser scanning activity performed presently on the physical building in creating a model in BIM environment. The result gives an overview about tracking information on changes within a historical building as part of cultural heritage management. This paper finds that by modelling the data captured by the 3D laser scanner and utilizing the existing data, BIM is capable of helping managers to retrieve, analyze and store important information in a more efficient and productive process. This exploration is substantial as a precursor to a much broader study on BIM for cultural heritage in the Malaysian context. As BIM is set to drive the construction industry, the finding made would be a catalyst for creating awareness to support the development of BIM for cultural heritage management in Malaysia.